Enhancing the welfare of beginner rabbit farmers through integrated farming systems - Arman, Arman; Rosidah, Ainur; Kholidah, Umi (Universitas Muhammadiyah Magelang, 2025)
Low productivity and limited technical knowledge are primary obstacles for beginner rabbit farmers in Kalidadi Village, Central Lampung. This community service program, through the POHON OPIUM initiative, aims to enhance farmer capacity through appropriate technology application and institutional strengthening. The methodology employed a community-based empowerment approach involving technical-managerial training, integrated cage installation, and continuous mentoring. Results indicated significant increases in knowledge (83.5%), skills (87.5%), and active participation (62.8%). The economic impact included an average income growth of 59.1% within three months through livestock sales and waste diversification into liquid organic fertilizer and planting media. The program's success was further evidenced by the institutional strengthening of the Kakabit Farm group through a breeder rotation system and collective savings. The integration of technological innovation and circular economy principles proved effective in enhancing farmers' economic independence while establishing an environmentally friendly cultivation system.